Saltwater intrusion ecophysiological effects on Pseudophoenix sargentii, Roystonea regia, Sabal palmetto “Lisa,” and Thrinax radiata in South Florida - Khoddamzadeh, Amir Ali; Flores, Jason; Griffith, M. Patrick; Souza Costa, Bárbara Nogueira (Frontiers in Ecology and Evolution, 2023)
Climate change will alter natural areas on a global scale within the next century, especially in low-lying coastal areas where sea-level rise is predicted to severely degrade or destroy many ecosystems. As sea-level rise continues, it is expected that salinity due to saltwater intrusion will impact soil health and agricultural production, this is of even greater importance in areas such as South Florida where the surface and groundwater resources are hydrologically connected due to the shallow and highly permeable limestone soils. The chlorophyll concentrations in leaf tissue were chosen as the primary health indicator to assess whether this is a valuable factor to consider for plant health risk assessment and whether optical sensor technology such as the SPAD and NDVI, are valuable tools when understanding the impact seawater encroachment has on plant nitrogen uptake. Therefore, the aim of this study was to evaluate the effects of salt concentrations on plant growth and health of four palm species. The treatments were from pure reverse osmosis water, Fresh water, brackish water, seawater and hypersaline water (0, 0.5, 5, 10, 15, 25, and 50 ppt). Control treatment that received reverse osmosis filtrated water with a salinity concentration of 0 ppt had the highest health-indicator averages compared to treatment 50 ppt. As the salinity increased, all health indicators gradually declined or remained rather constant and declined as they approached the greater salinity concentrations. The growth parameters and chlorophyll content were reduced over time, particularly at higher salt concentrations for all palm species studied. The chlorophyll content by SPAD and the normalized difference vegetation index (NDVI) can be used as health indicators of the palm species studied, as it was observed in this study a decline in the chlorophyll content as there was an increase in salt concentrations. It is important to emphasize that leaf chlorosis and subsequent decline of palm species were observed in the treatment with higher salt concentration, thus highlighting the importance of chlorophyll content as an indicator of plant health. The species Roystonea regia was very susceptible to salinity, and the palm Sabal palmetto is more susceptible to salinity than the Thrinax radiata and Pseudophoenix sargentii palms.